Efficacy and safety comparison between silodosin and tamsulosin as medical expulsive therapy for distal ureteral stones - Rahman, Farhan Haidar Fazlur; Leonardo, Kevin; Ardaya, Radhyaksa; Atmoko, Widi; Parikesit, Dyandra (Medical Journal of Indonesia, 2023)
BACKGROUND Ureteral stones are a common urological condition causing significant discomfort and morbidity. Medical expulsive therapy (MET) is a noninvasive approach to facilitate the passage of stones. This study aimed to compare the efficacy and safety of silodosin and tamsulosin as MET in patients with distal ureteral stones (DUS). METHODS We searched CINAHL, Cochrane Library, PubMed, and ScienceDirect for randomized controlled trials (RCTs) on the administration of silodosin and tamsulosin for DUS. The primary outcomes analyzed were stone expulsion rates and expulsion times, measured as risk ratio (RR) and mean difference (MD), respectively. Statistical analyses were performed using Review Manager 5.4 and STATA 17. RESULTS 14 RCTs comprising 1,535 patients (770 received silodosin) met the inclusion criteria. The silodosin group had notably higher stone expulsion rates (RR 1.20, 95% confidence interval [CI] 1.13–1.27, p<0.00001, I² = 37%), shorter expulsion times (MD −2.98, 95% CI −4.35–−1.62, p<0.01, I² = 85%), and fewer colicky pain episodes (MD −0.35, 95% CI −0.59–−0.10, p<0.01, I² = 83%) than the tamsulosin group. Retrograde ejaculation was the only adverse event that had a significant difference between both groups, statistically favoring tamsulosin (RR 1.61, 95% CI 1.12–2.33, p = 0.01, I² = 0%). CONCLUSIONS Silodosin should be preferred as the first-line MET agent for DUS owing to its better expulsion rate, shorter stone expulsion time, and fewer colicky pain episodes. However, tamsulosin may be used in selected cases where patients experience retrograde ejaculation after receiving silodosin.